Examining the factors contributing to employee retention of BEXIMCO Pharmaceuticals: The case study on HR Department of BEXIMCO Pharma - Ashika, Mushfica Jahan (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.